2021
DOI: 10.5194/nhess-21-3573-2021
|View full text |Cite
|
Sign up to set email alerts
|

Using high-resolution regional climate models to estimate return levels of daily extreme precipitation over Bavaria

Abstract: Abstract. Extreme daily rainfall is an important trigger for floods in Bavaria. The dimensioning of water management structures as well as building codes is based on observational rainfall return levels. In this study, three high-resolution regional climate models (RCMs) are employed to produce 10- and 100-year daily rainfall return levels and their performance is evaluated by comparison to observational return levels. The study area is governed by different types of precipitation (stratiform, orographic, conv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 119 publications
0
21
0
Order By: Relevance
“…These single decadal climate realizations will however be strongly influenced by natural climate variability (Lehner et al, 2020;Leduc et al, 2019;Deser et al, 2012;Hawkins and Sutton, 2009). Poschlod (2021) has shown the suitability of the CRCM5-LE and highlights the added value of using a regional SMILE for the analysis of precipitation extremes even on non-convection permitting resolutions. Other studies have shown that the CRCM5-LE, even though convection is parameterized, can show a good representation of the timing of maximum annual precipitation (Wood and Ludwig, 2020), as well as good agreement for ten-year return levels of 3h-24h annual maxima with observations (Poschlod et al, 2021) over Europe.…”
Section: Discussionmentioning
confidence: 97%
“…These single decadal climate realizations will however be strongly influenced by natural climate variability (Lehner et al, 2020;Leduc et al, 2019;Deser et al, 2012;Hawkins and Sutton, 2009). Poschlod (2021) has shown the suitability of the CRCM5-LE and highlights the added value of using a regional SMILE for the analysis of precipitation extremes even on non-convection permitting resolutions. Other studies have shown that the CRCM5-LE, even though convection is parameterized, can show a good representation of the timing of maximum annual precipitation (Wood and Ludwig, 2020), as well as good agreement for ten-year return levels of 3h-24h annual maxima with observations (Poschlod et al, 2021) over Europe.…”
Section: Discussionmentioning
confidence: 97%
“…When distributing on too few hours, extreme hourly intensities evolve, which may have never occurred or may even be physically implausible. For temporal disaggregation of extreme precipitation, we recommend dynamical downscaling via high-resolution climate models (Poschlod, 2021;Poschlod et al, 2021;Zabel et al, 2012;Zabel and Mauser, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…So far for DDF curves in Germany, there is not objective quantification of the uncertainty, but only approximative guessed tolerance ranges between 10-20% (depending on the return period) that should account for the measurement errors, uncertainties in the extreme value estimation and regionalisation, and for the climate variability (Junghänel et al, 2017). So far in Germany, the tolerance ranges are kept constant throughout duration levels and locations, nevertheless such tolerance ranges are expected to be higher for very short observations and high return periods (Poschlod, 2021) especially for short durations and drier climate (Marra et al, 2017). Therefore, there is a need to perform different simulations in order to quantify the tolerance ranges (uncertainty) dependent on duration, location and return period.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the focus is on developing a framework that accounts for uncertainties due to short observation lengths and non-representativeness of point measurements. Once a framework is developed, it can be used to investigate the role of distribution choice as in Miniussi and Marra (2021) or the role of future climate as in Poschlod (2021).…”
Section: Introductionmentioning
confidence: 99%